Hysteretic Behavior of Prestressed Concrete Bridge Pier with Fiber Model - Wang Hui-li; Feng Guang-qi; Qin Si-feng (The Scientific World Journal)
The hysteretic behavior and seismic characteristics of the prestressed concrete bridge pier were researched. The effects of the prestressed tendon ratio, the longitudinal reinforcement ratio, and the stirrup reinforcement ratio on the hysteretic behavior and seismic characteristics of the prestressed concrete bridge pier have been obtained with the fiber model analysis method. The analysis show some results about the prestressed concrete bridge pier. Firstly, greater prestressed tendon ratio and more longitudinal reinforcement can lead to more obvious pier’s hysteresis loop “pinching effect,” smaller residual displacement, and lower energy dissipation capacity. Secondly, the greater the stirrup reinforcement ratio is, the greater the hysteresis loop area is. That also means that bridge piers will have better ductility and stronger shear capacity. The results of the research will provide a theoretical basis for the hysteretic behavior analysis of the prestressed concrete pier.